IMF Staff papers : Volume 3 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1954)
This paper presents a study on economic development with stability in India. While the Five-Year Plan occupies the central position as the means through which the Government of India proposes to deal with the basic economic problem, it must be implemented by many specific economic and social measures. It is of the utmost importance that the measures taken in various fields should not only contribute to the fulfilment of the Five-Year Plan but that they should form part of a consistent economic and social policy. Apart from the change in total foreign investment, the composition of foreign investment in India now includes a larger proportion of direct and a smaller proportion of fixed interest obligations than before the war. While India's official sterling debt has been practically wiped out, the Government of India has incurred new obligations in dollars. If India could meet its pre-war obligations on foreign investment without any great strain on its balance of payments, it should be able to meet future obligations, resulting from any new debts, provided its balance of payments position in the future is not materially worse than in the past.